The influence of 3x3 bonded retainer on anterior crowding relapse in mandibular incisor extraction cases - Marcelo BERBERT; Paula COTRIN; Renata Cristina Gobbi de OLIVEIRA; Ricardo Gobbi de OLIVEIRA; Fabricio Pinelli VALARELLI; Marcos Roberto de FREITAS; Karina Maria Salvatore FREITAS (Dental Press Editora, 2021)
ABSTRACT Objective: To evaluate the 3x3 bonded retainer influence on the mandibular anterior crowding in cases treated with mandibular incisor extraction Methods: The sample comprised pretreatment, posttreatment and follow-up orthodontic records of 16 subjects (10 females and 6 males) with Class I malocclusion treated with extraction of a single mandibular incisor. The mean ages (± SD) at pretreatment, posttreatment and follow-up evaluation were 23.45 ± 9.14 years, 25.50 ± 8.95 years and 30.11 ± 8.59 years, respectively. The mean (± SD) treatment time and posttreatment evaluation time were 2.05 ± 0.45 years and 4.60 ± 1.85 years , respectively. Little irregularity index and interdental widths were evaluated using dental casts. The sample was divided into two subgroups, according to the presence of the 3x3 bonded retainer at follow-up. Results: The subgroup without 3x3 bonded retainer presented a greater relapse at the follow-up, when compared to 3x3 bonded retainer subgroup. Conclusion: There was a significant relapse in cases treated with mandibular incisor extraction at follow-up. The subgroup without 3x3 bonded retainer showed a significant relapse at the follow-up when compared to the retainer group.